Improving high-intensity intermittent running performance and repeated-sprint and jump ability in young elite female handball players: to lift or to play? - Buchheit, M.; Leblond, F.; Buchheit, J.; Renaud, C. (Sport Performance & Science Reports, 2017)
High-intensity intermittent running capacity and repeated sprint and jump ability are important components of physical performance in elite Handball (1, 2). While the most efficient training methods likely involve a combination of strength, speed and metabolic conditioning (1, 3), those training objectives may have superior effects when targeted in isolation than combined (4) (known as the toothpaste theory). Nevertheless, the distinct effects of a strength/speed (aimed at improving the first sprint or jump efforts) vs. sport-specific metabolic (aimed at improving the ability to repeat those efforts) training program are unknown. Aim.The aim of the present study was to compare the effect of supplementing usual technical/tactical handball training contents with a gym-based strength/speed (5) vs. small-sided handball games (SSG) (6) on high-intensity intermittent running capacity and repeated sprint and jump ability.